Elementary School Teachers Teaching Trends in Thematic Lessons on Social Media - Ali, A. Muh.; Suherman, La Ode Achmad; Suarti; Masri; Komaria, Nur Aulia; Asdar, A.Fathul (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
Social media, particularly Facebook, has become one of the primary platforms for teachers to interact, share, and find inspiration related to education. On Facebook, numerous active education groups and pages exist where teachers share teaching materials, teaching experiences, and instructional strategies. Observing the evolving trends in thematic learning, it is crucial to understand how materials and teaching strategies related to thematic learning in elementary school are communicated and shared in the online world, especially on the Facebook platform. Therefore, this research aims to analyze the teaching materials and strategies of elementary school teachers related to thematic learning in the digital realm, specifically on Facebook. This study will identify the latest trends in thematic learning and explore various approaches and ideas proposed by teachers in the virtual environment. The findings of this research are expected to provide a comprehensive overview of how elementary school teachers leverage the Facebook platform to support and enhance the thematic learning process, contributing positively to the development of education at the elementary school level. With knowledge of the most relevant and effective teaching materials and strategies circulating online, educators and policymakers in the field of education can benefit from the findings of this research to improve the quality of elementary education and support teachers in addressing the challenges of learning in the digital era.